The Role of Prosocial Communities in Youth DevelopmentThe Role of Prosocial Communities in Youth Development - Tyler, Forrest B. (Psykhe, 2004)
Providing a supportive prosocially oriented socialization for children was emphasized as necessary for their development as responsible citizens oriented to living in and sustaining their communities. A prosocial community was defined as one in which its inhabitants are concerned with the well-being of others in the community and the community as well as with themselves. The failure of current community psychology theory, research, and projects to address the nature of communities and implications of their work for the development of prosocial communities and children was addressed. A comprehensive child-centered approach to prosocial community building which necessarily includes children as participants was outlined. Illustrative youth oriented prosocial community projects, implications of their outcomes, and suggested research directions were cited.